Using a realist approach to explain outdoor activities and mobility in care homes: the ROAM Study - King, A.L. (2018)
Background: Whilst outdoor activities and mobility are believed to be beneficial for older care home residents, UK best practice guidance is based on occupational therapy-led expert consensus. This thesis reports research which aimed to provide theory-driven explanations about residents’ occupational engagement in the gardens and outdoor spaces of UK care homes.